Audit Keamanan Sistem Informasi Pada Data Center Menggunakan Standar SNI-ISO 27001 - Syafrinal, S; Agusrijar, A (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Information system security management is very important for Aceh Government institutions in managing information assets that refer to a standard. This will have a negative impact on the sustainability of information services, especially e-mail services managed by the Aceh Communication, Information, and Encryption Service. So the need for good management governance according to national and international standards to create good management of electronic mail information system services by conducting an internal audit process on its management in terms of physical and environmental security where the electronic mail service information system is managed. This study discusses the